ANALYSIS OF TRAFFIC LIGHTING ON ROAD USERS: CASE STUDY OF SILIWANGI ROAD KADIPATEN - MAJALENGKA - Yusan Nurul Septiyani; Indrastuti (LEADER: Civil Engineering and Architecture Journal, 2024)
A well-lit and safe roadway is a crucial factor in ensuring the safety and comfort of road users. This research presents an in-depth analysis of traffic lighting on Jalan Siliwangi Kadipaten-Majalengka through a comprehensive case study. The main focus of the study was to understand the impact of lighting levels on road user behavior concerning infrastructure conditions and lighting aspects. The research methodology involved a field survey that included measuring light intensity, monitoring the type of lights used, and evaluating infrastructure conditions related to street lighting. In addition, a questionnaire from road users was also conducted to obtain their perceptions and experiences regarding traffic lighting along the road. The results show that there are variations in the level of illumination on different parts of the road, which may affect the level of alertness of road users. The analysis of road user behavior also provides insights into the direct impact of lighting conditions on speed, distance judgments, and responses to traffic situations. Based on these findings, the research provides recommendations for the improvement of the street lighting system by considering more efficient use of lights, regular maintenance, and adequate infrastructure adjustments. This research is expected to contribute significantly to the development of strategies that can improve road user safety and comfort on Jalan Siliwangi Kadipaten-Majalengka, as well as provide a foundation for further research in the traffic lighting domain.